2016
DOI: 10.1002/ajoc.201600169
|View full text |Cite
|
Sign up to set email alerts
|

Ti‐Mediated Efficient Reductive Dehalogenation of Carbon–Halogen Bonds

Abstract: A mild and efficient methodology for the reductive dehalogenation of carbon-halogen bonds in both activated (allylic or benzylic) and non-activated halides with excess Ti III is thoroughly described. A detailed computational and experimental study corroborates that the reaction occurs via the allyl(benzyl) radical and allyl(benzyl)-Ti, which is protonated by a Brønsted acid, and proceeds regioselectively in the case of allylic derivatives. This synthetic method is compatible with a wide range of functional gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…In the seminal works reported by Nugent and Rajanbabu, it was observed that Cp 2 TiCl was a novel single-electron transfer species capable of generating a radical from an epoxide, which under different experimental conditions could give cyclization reactions, intermolecular additions, reductions, and deoxygenation reactions. From this moment, this SET was widely used in chemical synthesis, meeting if not all, at least many of the 12 principles reported for Green Chemistry.…”
Section: Cp2ticl As a Green Chemistry Reagentmentioning
confidence: 99%
See 2 more Smart Citations
“…In the seminal works reported by Nugent and Rajanbabu, it was observed that Cp 2 TiCl was a novel single-electron transfer species capable of generating a radical from an epoxide, which under different experimental conditions could give cyclization reactions, intermolecular additions, reductions, and deoxygenation reactions. From this moment, this SET was widely used in chemical synthesis, meeting if not all, at least many of the 12 principles reported for Green Chemistry.…”
Section: Cp2ticl As a Green Chemistry Reagentmentioning
confidence: 99%
“…The Cp 2 TiCl complex can interact with epoxides, ozonides, oxetanes, allylic and propargylic halides, saturated ketones, imines, α-haloketones, unactivated alkyl halides, and α,β-unsaturated and aromatic aldehydes and ketones to yield the corresponding carbon-centered radicals (Scheme ). As we have already mentioned, the way in which these carbon-centered radicals progress depends upon the reaction conditions.…”
Section: Reactivity Of Cp2ticl In Organic Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Thus alkanes were obtained from primary aliphatic halides, primary and secondary benzylic halides, and secondary allylic halides whereas primary allylic halides gave alkene derivatives (Scheme 5). 31…”
Section: Timentioning
confidence: 99%
“…The regioselectivity obtained was again explained by the coordination of the Brönsted acid to the titanium atom of 16. 31…”
Section: Scheme 5 Dehalogenation-reduction Reactions Promoted By Cp 2mentioning
confidence: 99%